1988
DOI: 10.1093/nar/16.10.4419
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of nuclear factor I/DNA interactions

Abstract: Nuclear factor I (NFI) was purified to homogeneity from porcine liver by DNA-affinity chromatography and displays a single band with a molecular weight of 36 kDa in SDS-polyacrylamide gels. The purified protein was used to determine absolute equilibrium binding constants by gel retardation techniques for a variety of DNA fragments with genuine or mutated NFI binding sites and a number of DNA fragments derived from various eukaryotic promoters carrying the CCAAT-box as a half-site for NFI binding. We present a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 37 publications
3
72
0
Order By: Relevance
“…The (p50)2 form, and perhaps (p52)2 in some cells, detected in the nuclei of many cell types as KBF-1 (Isra61 et al 1987), activates certain KB sites constitutively and should be subject to coactivation by BCL-3. Because the p50 homodimer has an extremely high affinity for DNA binding (Kd --5 pM) (Zabel et al 1991;Fujita et al 1992), as compared with other eukaryotic DNA-binding proteins (Kd --10--100 riM) (Chodosh et al 1986;Meisterernst et al 1988;Harada et al 1989;Cao et al 1991), it might bind effectively to chromosomal DNA but not function as a strong activator. The coactivator BCL-3 could then easily recognize the bound (p50)2 and interact with it.…”
Section: Gene Regulation By P50 and Bcl-3mentioning
confidence: 99%
“…The (p50)2 form, and perhaps (p52)2 in some cells, detected in the nuclei of many cell types as KBF-1 (Isra61 et al 1987), activates certain KB sites constitutively and should be subject to coactivation by BCL-3. Because the p50 homodimer has an extremely high affinity for DNA binding (Kd --5 pM) (Zabel et al 1991;Fujita et al 1992), as compared with other eukaryotic DNA-binding proteins (Kd --10--100 riM) (Chodosh et al 1986;Meisterernst et al 1988;Harada et al 1989;Cao et al 1991), it might bind effectively to chromosomal DNA but not function as a strong activator. The coactivator BCL-3 could then easily recognize the bound (p50)2 and interact with it.…”
Section: Gene Regulation By P50 and Bcl-3mentioning
confidence: 99%
“…Purification of crude extracts by DEAE-cellulose and Mono-Q chromatography has been described recently (Meisterernst et al 1988a). Fractions were monitored by gel retardation assays using end-labeled synthetic oligonucleotides or isolated DNA fragments.…”
Section: Preparation and Purification Of Nuclear Extractsmentioning
confidence: 99%
“…The four members of this family, Nfia, Nfib, Nfic and Nfix, share a common DNA binding sequence. The NF-I transcription factors bind to the dyad symmetric consensus sequence TTGGCNNNNNGCCAA and to individual half-sites with reduced affinity (Gronostajski et al, 1985;Meisterernst et al, 1988). Previous studies have found that NF-I transcription factors preferentially bind DNA target sites that are located close to transcription start sites and mainly act as activators of transcription of downstream target genes (Pjanic et al, 2011).…”
Section: Introductionmentioning
confidence: 99%